2008
DOI: 10.1186/1742-4933-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell autonomous expression of inflammatory genes in biologically aged fibroblasts associated with elevated NF-kappaB activity

Abstract: Background: Chronic inflammation is a well-known corollary of the aging process and is believed to significantly contribute to morbidity and mortality of many age-associated chronic diseases. However, the mechanisms that cause age-associated inflammatory changes are not well understood. Particularly, the contribution of cell stress responses to age-associated inflammation in 'non-inflammatory' cells remains poorly defined. The present cross-sectional study focused on differences in molecular signatures indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 49 publications
9
44
0
Order By: Relevance
“…The results of our study suggest that cellular senescence in the lungs not only limits cell proliferation but promotes inflammation, corroborating the results of previous studies that showed increased production of proinflammatory cytokines by different types of cells, such as fibroblasts and endothelial cells, that underwent senescence in vitro [24,25,26]. The overproduction of IL-6, IL-8 and TNF-α by senescent alveolar epithelial cells observed in this study may result in the establishment of a positive feedback loop, since TNF-α, for example, activates NF-ĸB signaling in alveolar epithelial cells and thereby stimulates them to produce proinflammatory cytokines [27,28].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of our study suggest that cellular senescence in the lungs not only limits cell proliferation but promotes inflammation, corroborating the results of previous studies that showed increased production of proinflammatory cytokines by different types of cells, such as fibroblasts and endothelial cells, that underwent senescence in vitro [24,25,26]. The overproduction of IL-6, IL-8 and TNF-α by senescent alveolar epithelial cells observed in this study may result in the establishment of a positive feedback loop, since TNF-α, for example, activates NF-ĸB signaling in alveolar epithelial cells and thereby stimulates them to produce proinflammatory cytokines [27,28].…”
Section: Discussionsupporting
confidence: 80%
“…The second limitation is that we do not know whether other types of pulmonary cells, such as endothelial cells and fibroblasts, also exhibit a proinflammatory phenotype when they become senescent. In this context, recent studies have shown constitutive activation of inflammatory pathways in senescent human umbilical vein endothelial cells [25] and senescent skin fibroblasts [26]. In the present study, we also found that senescent HDMECs produced greater amounts of IL-6, IL-8 and TNF-α than presenescent HDMECs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, the percentage of EGFP + cells was 35% lower in the spleens of Ercc1 -/-NF-κB EGFP mice than in those of WT NF-κB EGFP littermates, indicating that NF-κB activation is not exclusively driven by inflammation. These data support earlier reports (22,23) that there is increased NF-κB activation with mammalian aging and extend this to include a murine model of XFE progeroid syndrome, which is driven by a DNA repair defect.…”
Section: Figuresupporting
confidence: 79%
“…Moreover, NF-κB is up-regulated in tissues of aged rodents, specifically in the skin, liver, kidney, cerebellum, cardiac muscle and gastric mucosa (Bregegere et al, 2006;Giardina and Hubbard, 2002;Helenius et al, 1996a;Helenius et al, 1996b;Korhonen et al, 1997;Xiao and Majumdar, 2000). Cells derived from elderly persons and patients with Hutchinson-Gilford progeria, a disease of dramatically accelerated aging, also exhibited increased NF-κB signalling (Adler et al, 2007;Boland, 2001;Kriete et al, 2008). Growing evidence indicates that NF-κB becomes activated in aged tissues in response to accumulated damage and mediates the degenerative changes.…”
Section: Role Of Chronic Activation Of Nf-b In Diseasesmentioning
confidence: 99%